Problematika Perbankan Syariah: Solusi dan Strategi Digitaliasasi dalam Meningkatkan Kualitas Produk dan Layanan Perbankan di Bank Sumut Kantor Cabang Syariah Medan - Mardia Shintia Devi Gultom; Mustapa Khamal Rokan (Postgraduate, University of Mataram, 2022)
The purpose of this research is to find out appropriate strategies through the digitization of products and services in order to improve the quality of Islamic banking and be better known by the wider community. The aspects analyzed are islamic banking problems. The synthesis described is the solution and strategy of developing Islamic banking through the role of digitalization in improving the quality of Islamic banking products and services. Among the development strategies of Bank Sumut Syariah Sharia Branch Office Medan, namely through payment and purchasement services and services, SUMUT Mobile, ATM Services, E-Martabe Cards, Strengthening the digitization system to improve the efficiency of Islamic banking services, strengthening human resources in improving the innovation of Islamic banking products, in addition, among the management of Islamic banking development through the use of information digitization is very important so that the existence of Islamic banking is very important so that the existence of Islamic banking is very important so that the existence of Islamic banking is very important so that the existence of Islamic banking is very important so that the existence of Islamic banking is very important so that the existence of Islamic banking the higher so that people's interest in using Islamic banking services and services is increasing